DEVELOPMENT OF SBAR COMMUNICATION AMONG NURSES IN APPLYING NURSING DOCUMENTATION TO IMPROVE PATIENT SATISFACTION AT H. SAHUDIN KUTACANE GENERAL HOSPITAL - ENDARA SUSANTI; INDAH NUR'AINI (JURNAL ILMIAH KOHESI, 2019)
Communication nurses using SBAR technique is an effective way to improve patient satisfaction and development of Nursing Care Documentation. The objective of this research is to know the application of SBAR communication among nurses on nursing documentation to improve patient's satisfaction. This study used quasi experimental design with Pre and Post- test without control. Besides, this research used simple random sampling technique with 97 respondents from nurses and 91 respondents from patient. The data were analysed by using Mc Nemarp application of nursing care documentation = 0,010 (p value <0,05, and, patient satisfaction = 0.004 (p value <0,05). The result shows that communication using SBAR technique influence patient satisfaction and execution of documentation of nursing care at Tanjung Pura General Hospital.In conclusion, this study shows that there is a positive impact of the implementation of SBAR communication in the documentation of nursing care which proves that an effective method to improve patient satisfaction. The researchers hope this SBAR communication technique can be a fixed procedure in communication and application of nursing care documentation, so it can improve patient satisfaction and will indirectly enhance quality of service in the hospital